1
$\begingroup$

I wonder if anyone knows a reference for this question:

For a complex matrix $A$ with only one eigenvalue $\lambda$ such that $||A^k || \leq C|\lambda|^k$ (for some constant $C$), can we say $A$ is diagonalizable?

$\endgroup$
3
$\begingroup$

The answer is yes. While the idea of the proof can usually be found in the development of Gelfand's formula, I don't think the result is stated as a theorem in many books.

In general, suppose $\lambda$ is one of the largest-sized eigenvalue of a complex square matrix $A$ (i.e. $|\lambda|=\rho(A)$). If there is a positive constant $C$ such that $\|A^k\|\le C|\lambda|^k$ for every positive integer $k$, then $\lambda$ must be semi-simple. (In your case, since $\lambda$ is the only eigenvalue, that $\lambda$ is semi-simple implies that $A$ is diagonalisable.)

Suppose the contrary. Then $Av=\lambda v$ and $Au=\lambda u+v$ for some eigenvector $v$ and generalised eigenvector $u$. It follows from mathematical induction that $A^ku=\lambda^ku+k\lambda^{k-1}v$. Now pick any vector norm $\|\cdot\|$ such that $\|au+bv\|=\max(\|au\|,\|bv\|)$ (e.g. take $\|x\|=\|P^{-1}x\|_\infty$ where $P$ is any invertible matrix whose first two columns are $u$ and $v$). Then it induces a matrix norm $\|M\|=\sup_{x\ne0}\frac{\|Mx\|}{\|x\|}$. Since all norms are equivalent on a finite-dimensional vector space, we may assume that this induced matrix norm is the one in the condition that $\|A^k\|\le C|\lambda|^k$. Thus $$ k|\lambda|^{k-1}\|v\|\le\|\lambda^ku+k\lambda^{k-1}v\|=\|A^ku\|\le\|A^k\|\|u\|\le C|\lambda|^k\|u\|\tag{1} $$ for every $k\ge1$. But this is impossible: if $\lambda=0$, $(1)$ is violated when $k=1$; if $\lambda\ne0$, $(1)$ is violated when $k$ is large. Thus $\lambda$ must be semi-simple.

$\endgroup$
0
3
$\begingroup$

$\newcommand{nrm}[1]{\left\lVert {#1}\right\rVert}\newcommand{abs}[1]{\left\lvert {#1}\right\rvert}$ Let $A$ be a triangulable matrix with exactly one eigenvalue $\lambda$, and let there be some $C>0$ such that $\nrm {A^k}\le C\abs\lambda^k$ for all $k\ge 1$.

If $\lambda=0$, then $A=0$ by considering $k=1$.

If $\lambda\ne0$, then, by hypothesis, $A-\lambda I$ is nilpotent, therefore $$\nrm{A^k}=\nrm{(\lambda I+(A-\lambda I))^k}=\nrm{\sum_{h=0}^s \lambda^{k-h}\binom kh (A-\lambda I)^h}$$ where $s$ is the least natural number such that $(A-\lambda I)^{s+1}=0$. \begin{align}\nrm{A^k}&=\nrm{\sum_{h=0}^s \lambda^{k-h}\binom kh (A-\lambda I)^h}\ge\\&\ge\nrm{\lambda^{k-s}\binom ks(A-\lambda I)^s}-\nrm{\sum_{h=0}^{s-1}\lambda^{k-h}\binom kh(A-\lambda I)^h}\ge\\&\ge\abs\lambda^k\left(\nrm{\lambda^{-s}(A-\lambda I)^s}\abs{\binom ks}-\sum_{k=0}^{s-1}\abs{\binom kh}\nrm{\lambda^{-h}(A-\lambda I)^h}\right)\end{align}

Now, $\nrm{\lambda^{-h}(A-\lambda I)}$ for $h=0,1,\cdots, s$ are non-zero constants that depend on $A$ and $\lambda$. On the other hand, all the $\binom kj$ are polynomials (exactly) of degree $j$ in $k$. Therefore, $\frac1{\abs\lambda^k}\nrm{A^k}$ grows asymptotically at least as fast as some polynomial of degree $s$. Therefore the hypothesis demands $s=0$, which implies $(A-\lambda I)^{0+1}=0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.